Study the substitution of fossil fuels by RDF produced from municipal solid waste of HaNoi : M.A Thesis: Waste management and contaminated site treatment - Nguyễn, Bích Ngọc (University of Languages and International Studies, 2017)
53 p. + không có CD-ROM